Macroautophagy in T Lymphocyte Development and Function - He, You-Wen; He, Ming-Xiao; Mcleod, Ian; Jia, Wei (Frontiers in Immunology, 2012)
Macroautophagy (referred to as autophagy) is a fundamental intracellular process characterized by the sequestration of cytoplasmic compartments through double-membrane vesicles, termed autophagosomes. Recent studies have established important roles of autophagy in regulating T lymphocyte development and function. Resting T lymphocytes have basal levels of autophagy that is upregulated by TCR stimulation. Several specific knockout or transgenic models have been developed during the past few years, and it has been revealed that autophagy plays an essential role in regulating thymocyte selection, peripheral T cell survival and proliferation. The regulation of T cell development and function by autophagy is mediated through its role in regulating self-antigen presentation, intracellular organelle homeostasis and energy production. Here we will review the current findings concerning how autophagy regulates T cell function, as well as compare different models in studying autophagy in T lymphocytes.